2021
DOI: 10.3390/vaccines9050481
|View full text |Cite
|
Sign up to set email alerts
|

What Arguments against COVID-19 Vaccines Run on Facebook in Poland: Content Analysis of Comments

Abstract: Social media allow anti-vaxxers to quickly spread misinformation and false statements. This situation may lead to an increase in vaccine hesitancy. We wanted to characterize what arguments against COVID-19 vaccines run on Facebook in Poland. We analyzed Facebook comments related to the five events of the introduction of COVID-19 vaccines—announcements of the efficacy of the Pfizer-BioNTech (09.11.2020), Moderna (16.11.2020), and AstraZeneca (23.11.2020) vaccines, registration of the Pfizer-BioNTech vaccine by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 45 publications
(49 reference statements)
1
55
0
Order By: Relevance
“…It should be noted, however, that one of the Polish studies [ 17 ] was partially interventional (an interview induced by information presented to the respondent on vaccination and COVID-19). Thus far, apart from the studies discussed above, most of the Polish studies on COVID-19 vaccine hesitancy have focused on selected professional [ 47 , 48 ] and societal groups [ 49 , 50 ]. Our study addresses the problem of vaccine hesitancy in the broadest way through multivariate statistical modeling, and primarily refers to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that one of the Polish studies [ 17 ] was partially interventional (an interview induced by information presented to the respondent on vaccination and COVID-19). Thus far, apart from the studies discussed above, most of the Polish studies on COVID-19 vaccine hesitancy have focused on selected professional [ 47 , 48 ] and societal groups [ 49 , 50 ]. Our study addresses the problem of vaccine hesitancy in the broadest way through multivariate statistical modeling, and primarily refers to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Survey development was informed by the extant literature on COVID-19, vaccines against COVID-19, and vaccine readiness and hesitation among medical staff and medical and nursing students. The survey was also based on our previous research experience [27]. The questionnaire consisted of the following three sections: A total of 18 items in the survey included the following demographics: year and level of the program, sex, age, place of residence, chronic illnesses, flu vaccine uptake, career plans, the undertaking of student internships in departments treating COVID-19 patients, information about contracting COVID-19 (for the study participant and/or their immediate family), the course of the disease, information on receiving the vaccine, vaccination site, and the occurrence of adverse postvaccination reactions.…”
Section: Instrumentsmentioning
confidence: 99%
“…The other Polish study conducted at the beginning of the pandemic indicated that over 10% of surveyed Poles believed that SARS-CoV-2 was created by pharmaceutical companies [57]. Moreover, the analysis of Facebook users' comments posted on the selected Polish media profiles in November and December 2020 indicated that 85% of content related to the COVID-19 vaccines was negative with numerous conspiracy theories such as that the vaccines were created only for the profit of pharmaceutical companies or that the vaccines were already prepared before the pandemic [58]. This may also explain, at least partially, the high level of vaccine hesitancy seen in the Polish population right before and after the authorization of the first COVID-19 vaccines [59,60].…”
Section: Discussionmentioning
confidence: 99%